The Drivers of Credit Default Swap Prices: Evidence from Selected Emerging Market Countries - Ertugrul, Hasan Murat; Ozturk, Huseyin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
In this study, we empirically investigate the relationship between credit default swap (CDS) spreads and financial market indicators belonging to bond, equity, and foreign exchange markets for the selected emerging market countries. This study has several findings. The empirical results suggest that the CDS spreads have a cointegrating relationship with the remaining financial market indicators for the whole sample. Another finding that deserves particular attention is that in the long run, the CDS spread is negatively related with the CDS market uncertainties. We argue that this negative relationship indicates low liquidity in the elevated uncertainty, which decreases CDS prices. The time-varying effects of each variable on the CDS spread are in line with the results obtained from the cointegration analyses. These findings have several implications for investors and policymakers in emerging market countries.
Keywords: ARDL; bounds test; CDS price volatility; Kalman filter; SWARCH; EXCHANGE-RATE VOLATILITY; STOCK-MARKET; SOVEREIGN; REGIME; RATES; RISK; DETERMINANTS; INFLATION; CRISIS; MODEL; Business & Economics; International Relations